Методики чистого коду та їх користь для програмістів - Лисенко, Д. О. (ХНУРЕ, 2025)
Clean code techniques help you write code that is easy to understand and maintain. Their implementation allows you to extend the code without any problems, reduce the number of errors, and increase the reliability of the product. Developers’ understanding of these principles helps to unify their work so that it is as clear as possible for other programmers. We consider three clean code techniques that provide significant advantages when creating a software product.
Keywords: чистий код; методика чистого коду